Exploratory spatial data analysis with GEOXP - Ines Heba; Eric Malin; Christine Thomas-Agnan (European Regional Science Association (ERSA), 2002)
GEOX is a computer package of Splus and Matlab routines implementing interactive graphics methods for exploring spatial data. We analyse a large data basis from the regional public health insurance agency concerning physicians' activity in the Midi-Pyrénées region. We evaluate in particular heterogeneity and outliers in the density of physicians, their prescriptions per patient, salaries, number of visits per patient, etc.. We examine spatial dependencies of the main variables and thus locate spatial clusters. We attempt to explain the patterns of the prescription by some characteristics of the physicians together with the socio-economic characteristics of the counties using a spatial regression model with autocorrelated errors involving a hierarchical structure since these two sets of variables are known at a different level: physician level or county level.
Keywords: 330